Pollen Development and Viability in Diploid and Doubled Diploid Citrus Species - Lora, Jorge; Garcia-Lor, Andres; Aleza, Pablo (Frontiers in Plant Science, 2022)
Seedlessness is one of the most important agronomic traits in mandarin on the fresh fruit market. The creation of triploid plants is an important breeding strategy for the development of new commercial varieties of seedless citrus. To this end, one strategy is to perform sexual hybridizations with tetraploid genotypes as male parents. However, while seed development has been widely studied in Citrus, knowledge of the key steps, such as microsporogenesis and microgametogenesis, is scarce, especially in polyploids. Therefore, we performed a study on the effect of ploidy level on pollen development by including diploid and tetraploid (doubled diploid) genotypes with different degrees of pollen performance. A comprehensive study on the pollen ontogeny of diploid and doubled diploid `Sanguinelli´ blood orange and `Clemenules´ clementine was performed, with a focus on pollen grain germination in vitro and in planta, the morphology of mature pollen grains using scanning electron microscopy (SEM), the cytochemical characterization of carbohydrates using periodic acid-Shiff staining and specific cell wall components revealed by immunolocalization. During microsporogenesis, the main difference between diploid and doubled diploid genotypes was the cell area, which was larger in the doubled diploid genotypes. However, after the increase in size and vacuolization of the microspores, but before mitosis I, doubled diploid `Clemenules´ clementine showed drastic differences in shape, cell area and starch hydrolysis, which resulted in shrinkage of pollen grains. The loss of fertility in doubled diploid `Clemenules´ clementine is mainly due to a lack of carbohydrate accumulation in pollen during microgametogenesis, especially the starch content, leading to pollen grain abortion. All these changes make pollen of this genotype unviable, and very difficult to use as a male parent in sexual hybridizations with the objective to recover large progenies of triploid hybrids.